2022
DOI: 10.18251/ijme.v24i2.2827
|View full text |Cite
|
Sign up to set email alerts
|

Challenges for Teachers Working in Mainstream Schools with Culturally and Linguistically Diverse Students in Chile: Two Case Studies

Abstract: Recently, Chile has experienced a significant increase in linguistically and culturally diverse immigrants from Haiti. However, little is known about how Chilean teachers cope with this issue. Using Haworth’s (2009) model of contextual layers of teachers’ work as a conceptual lens, this article reports the findings from two case studies. Findings show that participants often struggled to teach their culturally and linguistically diverse students. These difficulties were attributed to teachers’ low levels of pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…However, Chilean teachers may lack the skills to teach students with different linguistic and cultural backgrounds. Parada and Tour (2022) conducted two case studies with a Math and an EFL teacher to analyse the challenges that Chilean school teachers faced when teaching students who did not speak Spanish nor English. Findings suggested that due to the communication barrier, the content was difficult to deliver, it was difficult to maintain learner engagement, and behaviours were misinterpreted in the classroom.…”
Section: Empirical Studies On Multiculturality Icc and Ismentioning
confidence: 99%
See 1 more Smart Citation
“…However, Chilean teachers may lack the skills to teach students with different linguistic and cultural backgrounds. Parada and Tour (2022) conducted two case studies with a Math and an EFL teacher to analyse the challenges that Chilean school teachers faced when teaching students who did not speak Spanish nor English. Findings suggested that due to the communication barrier, the content was difficult to deliver, it was difficult to maintain learner engagement, and behaviours were misinterpreted in the classroom.…”
Section: Empirical Studies On Multiculturality Icc and Ismentioning
confidence: 99%
“…The reviewed literature suggests that teachers in general hold positive views towards multicultural classrooms and that these attitudes help to develop respect and empathy (Kustati et al, 2020;Yilmaz, 2016) as well as healthier and safer learning environments (Castillo et al, 2020). However, multicultural classrooms come with challenges such as communication barriers (Parada & Tour, 2022) and lack of access to professional training (Choi & Mao, 2021). Most teachers across learning contexts display relatively high levels of IS (Boudouaia et al, 2022;Segura & Parra, 2019;Kazazoğlu & Ece, 2021;Mostafaei Alaei & Nosrati, 2018).…”
Section: Empirical Studies On Multiculturality Icc and Ismentioning
confidence: 99%